VISUAL ANALYTICS OF SMART CITY IOT: A FEDERATED MULTI-AGENT APPROACH TO SCALABLE AND PRIVACY-PRESERVING DATA SYSTEMS - Lavate, Santosh H.; Oruganti, Sai Kiran; Khan, Shakir; Moje, Ravindra K. (ShodhKosh: Journal of Visual and Performing Arts, 2026)
The centralized data processing methods encounter the issues of crucial challenges in terms of scalability, latency, communication overhead, and privacy leakage. In spite of federated learning progress, current solutions are mostly based on single-model coordination, and they are not adaptive to the intelligence, inter-agent coordination, and resilience to changing urban conditions. This leaves a gap in scalable, privacy-focused, and autonomous decision-making processes of real-time smart city operations. In an attempt to fill this gap, this paper presents a Federated Multi-Agent Intelligence (FMAI) platform, in which a number of intelligent agents are implemented on the IoT edge nodes. The local learning, contextual reasoning, and task-specific optimization are accomplished by each agent and a federated level of aggregation can share knowledge globally without exchange of raw data. The framework combines multi-agent learning reinforcement learning, adaptable model weighting, as well as secure aggregation to manipulate non-IID information, dynamic workloads, and privacy limitations. Its key contributions are: (i) a federated multi-agent framework that can support heterogeneous IoT settings with scalability, (ii) a privacy-aware cooperation framework that has lower communication cost, and (iii) an adaptable coordination approach that enhances the system-level intelligence, where cities are dynamic. Simulated smart traffic, energy and environmental monitoring data experimental analysis shows that the prediction accuracy improves by +28.7, communication overhead is reduced by -41.3, converges much faster +34.9, and reduces latency by +22.6 when using federated over centralized and single agent baselines. The privacy leakage risk, as indicated by membership inference accuracy, decreased by -52.1. These results substantiate the notion that federated multi-agent intelligence can be used to provide efficient, secure, and scalable data processing, and that it can serve as an effective background of next-generation smart city IoT ecosystems.